The story of Abraham’s hospitality in Biblical texts and in Palaea literature - A. B. Somov (Шаги)
This article investigates the story of Abraham’s hospitality in Gen 18:1–16, which became a kind of paradigm for behavior toward strangers in Judaism and Christianity as well as the source of mystical, Christological and Trinitarian interpretations. This story was further developed in later texts, among which the medieval Palaea literature (texts which combine biblical paraphrase, theology, and polemic, as well as some apocryphal legends) has to be specially emphasized. Unfortunately, this literature is often neglected by scholars dealing with Abraham’s hospitality. The article focuses on the story of Abraham’s hospitality in the context of this literature and related texts, as well as the possible influence of this tradition on Eastern Christian iconography. The article demonstrates that in this stratum of Christian tradition as well as in other exegetical works, the story about Abraham goes beyond the narrative of hospitality. In addition to concerns about the identification of the three strangers, which is a typical topic of Christian exegesis of Gen 18:1–16, in this literature, liturgical and Christological elements appear in the episode about Abraham’s fasting before the coming of the three strangers and in that about the resuscitation of the slaughtered and cooked calf which the patriarch earlier offered to his guests. The legend of Abraham’s refusal of food and water while waiting for guests is probably of Byzantine origin, while the account of the resurrection of the slaughtered calf may go back to an ancient Jewish source, which is also reflected in Test. Abr. A 6.4–5.